Lightning induced surges on an unenergized test overhead telecommunication subscriber line - Md. Golam Sorwar Hossain; Hussein Ahmad, 1953-; Annuar Mohd. Ramli; Nazmi Othman; M. M. Ali; P. Yahya; International Conference on Energy Management and Power Delivery (1998 : Singapore) (Skudai : Universiti Teknologi Malaysia, 1998)
03